The Strategy of Processing Coffee Farming System in Temas Mumanang Village Permata District of Bener Meriah Regency Nanggroe Aceh Darussalam - Puspitawati Puspitawati; Noviy Hasanah; Ayu Febryani (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This paper is about strategies for how to process coffee in the coffee farming system in Temas Mumanang Village, Permata District, Bener Meriah Regency, Nanggroe Aceh Darussalam Province. This paper thoroughly and in-depth describes the ways of planting and maintaining coffee plants carried out from the first period to the fourth period, starting from making coffee seeds, planting coffee seeds, maintaining coffee plants, and harvesting and handling post-harvest (processing). The whole period has special ways that are the local wisdom of Gayo coffee farmers. This local wisdom is used as a reference to the farming system which until now is able to make the Gayo High Region as a coffee producer with Robusta and Arabica Coffee varieties to foreign countries.